STRipy: A graphical application for enhanced genotyping of pathogenic short tandem repeats in sequencing data. Issue 7 (21st April 2022) - Halman, Andreas; Dolzhenko, Egor; Oshlack, Alicia
Abstract: Expansions of short tandem repeats (STRs) have been implicated as the causal variant in over 50 diseases known to date. There are several tools which can genotype STRs from high‐throughput sequencing (HTS) data. However, running these tools out of the box only allows around half of the known disease‐causing loci to be genotyped. Furthermore, the genotypes estimated at these loci are often underestimated with maximum lengths limited to either the read or fragment length, which is less than the pathogenic cutoff for some diseases. Although analysis tools can be customized to genotype extra loci, this requires proficiency in bioinformatics to set up, limiting their widespread usage by other researchers and clinicians. To address these issues, we have developed a new software called STRipy, which is able to target all known disease‐causing STRs from HTS data. We created an intuitive graphical interface for STRipy and significantly simplified the detection of STRs expansions. Moreover, we genotyped all disease loci for over two and half thousand samples to provide population‐wide distributions to assist with interpretation of results. We believe the simplicity and breadth of STRipy will increase the genotyping of STRs in sequencing data resulting in further diagnoses of rare STR diseases. Abstract : Software for easy detection of disease causing short tandem repeat expansions